(untitled) (Medical Forum Monthly, 2024)
Objective: The study was conducted to assess the awareness level about diabetes in patients coming to JPMC and to initiate steps to increase their knowledge and clear misconceptions. Study Design: Descriptive Cross-Sectional Study. Place and Duration of Study: This study was conducted in JPMC hospital from April 2008 to October 2008. Materials and method: A non- probability convenience sampling technique was applied in a population aged15<n<80(n=230) through which both diabetics and non-diabetics were interviewed after taking informed consent using a pre-structured questionnaire. Details regarding awareness about diabetes in relation to their knowledge on diabetes, causes, signs and symptoms, complications, treatment, diet, physical activity, degree of diabetes in the patient and measures to enhance their knowledge and health on the subject were accordingly marked. The data has been analyzed using SPSS 10.0. Results: In this study, 230 subjects irrespective of gender and age were assessed. 15% of the subjects were diabetics and most of them were unaware of the cause of the disease as well as of its complications, while the remaining 85% also had very little knowledge about diabetes and issues related to it. Conclusion: The level of awareness was generally low amongst the general population. The study reveals the essential need for strategies to create awareness regarding diabetes in the lower socio economic group. Diabetic patients were well informed about the disease they were suffering from.